Desain Interior Gereja Bethel Indonesia di Surakarta - Mega Puspa Susanto; IF. Bambang Sulistyono (Institut Seni Indonesia Surakarta, 2022)
Every individual who has trust, needs means and infrastructure in realizing their relationship with God. This can be realized by the construction of houses of worship. Church is a place of worship for Christians to ally with God, so this space is considered sacred. The problem of worship space of bethel church today is more looks like a concert hall than a place to worship. There are also other problems such as lack of wiggle room, children running around in the worship space, this can interfere with the course of worship. Therefore it takes space for Sunday school that can accommodate children to worship.The interior of the church has an important role in supporting one's need to worship. Based on the above concerns, a church was designed that could provide a sacred and peaceful atmosphere with the application of contemporary concepts, as well as design a Sunday school space that could appeal to children. There are also other rooms that serve as support rooms.